Gram-negative rods are associated with prolonged treatment in patients with thoracolumbar pyogenic spondylitis after minimally invasive posterior fixation compared with gram-positive cocci: a multicenter retrospective cohort study - Hisanori Gamada; Toru Funayama; Kengo Fujii; Yosuke Ogata; Yusuke Setojima; Takane Nakagawa; Takahiro Sunami; Kotaro Sakashita; Shun Okuwaki; Kaishi Ogawa; Yosuke Shibao; Hiroshi Kumagai; et al. (BMC Musculoskeletal Disorders)
Abstract Background This study compared patient characteristics, clinical outcomes, and antibiotic durations between patients undergoing posterior fixation for gram-negative rods (GNR) or gram-positive cocci (GPC) thoracolumbar pyogenic spondylitis. Methods In this multicenter retrospective cohort study, 53 patients who underwent minimally invasive posterior fixation for thoracolumbar pyogenic spondylitis were categorized into a GPC or GNR group based on the identified causative organisms. Patient characteristics, surgical outcomes, and postoperative infection control were compared between the two groups to identify factors affecting antibiotic duration. Results The patients in the GNR group (n = 14) were older (77.2 years versus 70.1 years; p = 0.008), had a higher incidence of a history of abdominal-pelvic infections (4 versus 0; p = 0.003), required longer preoperative antibiotics (5.9 weeks versus 3.0 weeks; p = 0.035), and had more unplanned additional surgeries due to poor infection control (n = 4 versus n = 1; p = 0.014) than those in the GPC group (n = 39). Furthermore, GNR infection independently predicted longer preoperative antibiotic duration (p = 0.002, β = 0.43). Conclusions Pyogenic spondylitis with GNR is associated with the need for prolonged antibiotic treatment and higher rates of unplanned additional surgeries due to poor infection control as compared to GPC-associated pyogenic spondylitis. Older age and a history of abdominal-pelvic infections tend to complicate the management in these patients; therefore, tailored treatment strategies are required to optimize treatment duration and minimize complications. Clinical trial number Not applicable.